Proceedings of the SIGCHI Conference on Human Factors in Computing Systems 2007
DOI: 10.1145/1240624.1240860
|View full text |Cite
|
Sign up to set email alerts
|

Provoking sociability

Abstract: In this study, we explore the potential usefulness of disturbing, uncomfortable systems, demonstrating that provocative technology can have a positive effect on social relationships. We designed and evaluated an agent-based system that collects user information by asking seemingly benign questions, and then uses it to spread false, strange gossip throughout an office space.We show that provocative interaction on-line can improve off-line sociability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Design noir provides a framework that stimulates reflections on the less desirable behaviour a product may engender. With very few exceptions (Foucault et al, 2007;Nathan et al, 2007), this framework has had little influence in HCI. The focus in this special issue on misuse intends to extend the design noir perspective to social agents, as their social nature adds to the complexity of the problem.…”
Section: Misusementioning
confidence: 99%
“…Design noir provides a framework that stimulates reflections on the less desirable behaviour a product may engender. With very few exceptions (Foucault et al, 2007;Nathan et al, 2007), this framework has had little influence in HCI. The focus in this special issue on misuse intends to extend the design noir perspective to social agents, as their social nature adds to the complexity of the problem.…”
Section: Misusementioning
confidence: 99%
“…Their actions could however affect human social relations in a direct way. Foucault et al [2] showed that a 'gossiping' agent spreading rumors gathered from its users can increase positive sociability between its users. People recommenders also already 'arrange' social contact (e.g.…”
Section: Introductionmentioning
confidence: 99%